Dietary phosphorus burden increases cariogenesis independent of vitamin D uptake. Issue 167 (March 2017) - Goodson, J. Max; Shi, Ping; Mumena, Chrispinus H.; Haq, Afrozul; Razzaque, Mohammed S.
Highlights: Correlation exists between calorie-adjusted phosphorus intake and dental decay. Children consumed low sugar but high phosphorus diet developed dental decay. Decayed teeth positively associated with increased salivary levels of adiponectin. Decayed teeth positively associated with increased salivary levels of MMP-9. Decayed teeth negatively associated with salivary levels of VEGF. Dietary phosphorus burden increases cariogenesis. Abstract: An association between excessive sugar consumption and dental decay, particularly in children, has been well-established. In this study we have analyzed whether consumption of phosphorus, an important ingredient of sugary drinks, has any association with the evolvement of dental decay. Food consumption, gingival redness and dental decay were evaluated in a total of 8, 317 children with the mean age of 9.99 + 0.68 years with a strong gender bias (p < 0.0005); boys being more affected than girls. Our results showed a significant association (p = 0.044) between dental decay and calorie-adjusted sugar intake. Presence of gingival inflammation also correlated (p = 0.008) with the formation of dental decay. In addition, decayed teeth were positively associated with increased salivary levels of adiponectin (p = 0.0002) and matrix degrading MMP-9 (p = 0.015), while negatively associated with salivary levels of the vascular endothelial growth factor (VEGF; p = 0.008). More importantly, we found a statistically significant correlation (p = 0.0008) between calorie-adjusted dietary phosphorus intake and occurrence of dental decay. Our analyzed results also showed a significantly high percentage of dental decay in children who consumed a diet, low in sugar but high in phosphorus (6.58%, n = 661), compared to those who consumed a low sugar and low phosphorus containing diet (5.02%, n = 413). Finally, we did not find any significant association between vitamin D uptake and the genesis of dental decay. From these results, we concluded that both high sugar and high phosphate consumption can influence evolvement of dental decay, and that, a healthier diet could be achieved by reducing consumption of dental cariogenic dietary factors, sugar and phosphate.